Clinico-epidemiological study of childhood lichen planus at a tertiary care centre in South India - Kambil, Srirath Madappally (International Journal of Research in Dermatology, 2018)
Background: Lichen planus (LP) is an autoimmune disorder occurring infrequently in children. LP is mainly seen in adults of both sexes. There are only a few studies on childhood LP in South India. Methods: 52 children under 14 years of age with LP were evaluated. The study was done in the Dermatology outpatient department from April 2016 to March 2018. The various clinical and epidemiological features observed are recorded in the study. Results: LP was slightly more common in boys and the age group mainly affected was 5-9years. Classical LP was the most common clinical type and extremities were the main site of skin lesions. Erosive lesions on buccal mucosa were the commonest type of mucosal involvement. Koebners phenomenon was seen in a significant number of cases. Conclusions: LP is not rare in children and resembles adult LP in most aspects. Mucosal and nail involvement is seen in many cases. Knowledge about the various clinical patterns of LP will help in early diagnosis and proper treatment.